The Disparity Between Willingness to Accept and Willingness to Pay Measures of Value - Coursey, Don L.; Hovis, John L.; Schulze, William D. (Quarterly Journal of Economics, 1987)
Don L. Coursey, John L. Hovis, William D. Schulze; The Disparity Between Willingness to Accept and Willingness to Pay Measures of Value*, The Quarterly Jou